Tingkat Pendidikan Dan Pengetahuan Pasangan Usia Subur Tentang Metode Kontrasepsi Jangka Panjang - Purnami, I Gusti Ayu Putu; Hindriyawati, Wiwin; Ekawati, Desi; Kismoyo, Christina Pernatun (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2023)
Long-acting reversible conceptions (LARCs) can be a solution to reduce poverty, unemployment and maternal mortality. The interest of couples of childbearing age in using LARC is still low. The low use of LARCs has resulted in the unmet need for family planning which caused by multiple factors. The purpose of this study was to determine the relationship between education level and knowledge of couples of childbearing age (CCA) about long-term contraceptive methods (LARCs) in Gupakwarak Hamlet, Sendangsari. This research is an analytic observational study using a cross-sectional design. The sampling technique used is simple random sampling with 134 respondents. The results showed that there is no significant relationship between education level and knowledge of fertile couples about LARC (p-value 0.109) in Gupakwarak Hamlet, Sendangsari. Knowledge is not only obtained through formal education but also from informal education such as counseling, actively seeking information on social media, antenatal classes, working environment, and/or counseling about LARC in Posyandu. It is recommended that midwives continue to provide counseling regarding LARC to pregnant women to provide consolidation regarding understanding of LARC, prevent misinformation, and help determine the right method for them.